Hubungan Antara Waktu Tunggu Pelayanan Resep dengan Kepuasan Pasien Rawat Jalan di Instalasi Farmasi Rumah Sakit Restu Ibu Balikpapan - Elza Yurika; Warrantia Citta Citti Putri; Rofidah Nur Umar (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2025)
Pharmaceutical services are an essential component in improving hospital service quality and patient satisfaction. One of the main indicators of pharmaceutical service quality is prescription waiting time. This study aimed to analyze the relationship between prescription waiting time and outpatient satisfaction levels at the Pharmacy Installation of Restu Ibu Hospital Balikpapan. This research employed a quantitative method with a cross-sectional design. The sample consisted of 393 outpatient respondents who met the inclusion criteria, with data collected through direct observation of prescription waiting time and a satisfaction questionnaire based on the five SERVQUAL dimensions (tangible, reliability, responsiveness, assurance, empathy). Data were analyzed using the Chi-Square test with a significance level of 0.05. The results showed that most prescription waiting times met the standard (≤30 minutes for non-compounded and ≤60 minutes for compounded drugs). The majority of patients expressed satisfaction with the services provided. The Chi-Square analysis revealed a significant relationship between prescription waiting time and patient satisfaction level p <0,001 (p < 0.05). Thus, shorter prescription waiting times are associated with higher levels of patient satisfaction.